2016
DOI: 10.1039/c6ra03516g
|View full text |Cite
|
Sign up to set email alerts
|

A diiodo-BODIPY postmodified metal–organic framework for efficient heterogeneous organo-photocatalysis

Abstract: A diiodo-BODIPY postmodified MOF acts as a highly active and recyclable heterogeneous photocatalyst for aerobic CDC and oxidation/[3 + 2]cycloaddition reactions under visible light irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Both noble transition metal and organic dye based photocatalysts have been successfully applied in various organic transformations. However, one disadvantage for this kind of homogeneous catalyst is the difficulty in recycling for multiuse. To solve the problem, one solution is to develop a heterogeneous photocatalyst for catalytic organic systhesis, and many achievements have been made in this field. Another option is to apply various types of support materials in immobilization of these homogeneous photocatalysts, such as polymers, silicas, graphene, and metal–organic frameworks (MOFs). Using materials in daily life as support for organic catalyst’s immobilizaition is quite interesting and more practical, but it is rare. In 2013, List et al reported the application of polyamide textiles as organocatalyst support for several catalytic organic transformations, to develop so-called “Organotextile Catalysis” .…”
Section: Introductionmentioning
confidence: 99%
“…Both noble transition metal and organic dye based photocatalysts have been successfully applied in various organic transformations. However, one disadvantage for this kind of homogeneous catalyst is the difficulty in recycling for multiuse. To solve the problem, one solution is to develop a heterogeneous photocatalyst for catalytic organic systhesis, and many achievements have been made in this field. Another option is to apply various types of support materials in immobilization of these homogeneous photocatalysts, such as polymers, silicas, graphene, and metal–organic frameworks (MOFs). Using materials in daily life as support for organic catalyst’s immobilizaition is quite interesting and more practical, but it is rare. In 2013, List et al reported the application of polyamide textiles as organocatalyst support for several catalytic organic transformations, to develop so-called “Organotextile Catalysis” .…”
Section: Introductionmentioning
confidence: 99%
“…A mechanism similar to the previous one was proposed to explain the formation of products 6 and 8 (See Scheme 3). A porous material‐immobilized iodo‐Bodipy dye has also been successfully employed in the oxidation/[3+2] cycloaddition/aromatization tandem reaction [29] while the groups of Li, Zhao, and Wang prepared a diiodo‐Bodipy postmodified metal‐organic framework which was applied to the aerobic reaction of N ‐aryl tetrahydroisoquinolines 1 with nitroalkanes 2 and the reaction of tetrahydroisoquinoline 4 with N ‐aryl and N ‐benzyl maleimides [30] . For both heterogeneous photocatalysts, recycling studies were carried out without a significant decrease in the yields after three reactions.…”
Section: Applications Of Bodipy In Photoorganocatalysismentioning
confidence: 99%
“…In this sense, for MOFs, the covalent anchorage of different photosensitizers (Vitamin B2 [68], BODIPY [69], Eosin Y [70] or subphtalocyanine [71]) has allowed the obtaining of heterogeneous photocatalysts that generally present higher stability and photocatalytic activity than their homogeneous versions (Figure 8). This enhancement can be due to the immobilization and isolation of photocatalytically active species, hampering unproductive encounters between photoexcited intermediates and, sometimes, leading to a change on the reaction mechanism.…”
Section: Functionalized Materialsmentioning
confidence: 99%
“…The same strategy was later employed by Khan and collaborators [70], who anchored the organic photocatalyst The functionalization strategy has also been applied in obtaining MOFs with photocatalytic activity for CDC reactions. Thus, a BODIPY photosensitizer was anchored to UiO-68 through pending amino groups present in the linkers [69]. The UiO-68-BP was employed as heterogeneous photocatalyst for CDC reactions among different N-aryl-THIQs and different nitroalkanes.…”
Section: Cross-dehydrogenative Couplingmentioning
confidence: 99%